Glucocorticoid receptor (NR3C1) genetic polymorphisms and the outcomes of sudden sensorineural hearing loss - Chen-Yu Chien; Shu-Yu Tai; Kuan-Hui Li; Hua-Ling Yang; Ling-Feng Wang; Kuen-Yao Ho; Ning-Chia Chang (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The glucocorticoid receptor gene (NR3C1) encodes the receptor to which cortisol and other glucocorticoids bind. Steroids in either oral, intratympanic, or intravascular forms are the treatment of choice for sudden sensorineural hearing loss (SSNHL), but the outcome varies. The outcomes of SSNHL have been investigated for related factors, including age, initial hearing loss severity and pattern, vertigo, genetic variations, and the time between onset and treatment. The objective of the present study was to analyze the association of genetic polymorphisms of NR3C1 with the outcomes of SSNHL. Materials and methods We conducted a comparison study of 93 cases with a poor outcome (control) and 100 cases with a good outcome (case) in SSNHL patients. Six single nucleotide polymorphisms (SNPs) were selected. The genotypes were determined using TaqMan technology. Results The heterozygous AT genotype of rs17100289 was associated with a poor outcome in comparison with the major homozygous AA genotype after adjustments for age and sex (OR = 0.50; 95% CI 0.26–0.95; P = 0.035) in SSNHL patients. The CT genotype of rs4912912 was also associated with a poor outcome compared with the major homozygous TT genotype after the adjustments (OR = 0.47; 95% CI 0.24–0.92; P = 0.026). Conclusion These results suggest that NR3C1 genetic polymorphisms may influence the outcomes of SSNHL. Graphical Abstract